Effect of Operating Variables on DMFC Performance for the Synthesized Si-PWA/PVA Nanocomposite Membrane - Pandey, Jay (Journal of Membrane and Separation Technology, 2016)
Electrochemical Performance of DMFC was studied under the effect of various operating parameters like temperature, methanol concentration and relative humidity (RH) for the synthesized silica immobilized phosphotungstic acid-poly(vinyl alcohol) (Si-PWA/PVA) nanocomposite membrane (thickness 80-100 µm). The optimized 1.5 Si-PWA/PVA membrane showed good electrochemical properties (transport number: 0.92 and IEC: 0.90 meq/g) with excellent mechanical strength, thermal and chemical stability. Open circuit voltage (OCV) decay was significantly lower in comparison to Nafion-117. Maximum power density (45.7 mWcm-2) was obtained at 60oC cell temperature. DMFC performance exhibited better performance even at higher methanol concentration (2 M) demonstrating lower concentration over potential. The appreciable rise in the peak power density observed at higher relative humidity (90%) showed good water stability of the membrane. Performance of the DMFC with the synthesized composite membrane was comparable to the state of the art Nafion-117.